A method for preparing absorbable material of hemostatic clip

By preparing a magnesium hydroxide coating on the magnesium alloy hemostasis clamp matrix and coating polydopamine, combined with modified polylactic acid, the problem of insufficient mechanical properties of polylactic acid hemostasis clamp and hazardous chemical substances after chemical treatment is solved, and a high mechanical properties and fully degradable hemostasis clamp material is achieved.

CN119770749APending Publication Date: 2025-04-08南京竹海生物科技有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510046138.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing polylactic acid hemostasis clips have insufficient mechanical properties, and the surface of the hemostasis clips after chemical treatment contains harmful chemicals, which extends the preparation time and poses potential harm to human health.

Method used

A magnesium alloy is used as a matrix, and a magnesium hydroxide coating is prepared on the surface of the magnesium alloy by hydrothermal treatment, and polydopamine is coated on the coating by chemical impregnation method, and finally combined with modified polylactic acid to form a hemostatic clamp material with good mechanical properties and completely degradable.

Benefits of technology

The prepared hemostatic clamp material has good mechanical properties, can completely degrade and absorb, has extremely little damage to the human body, and the degradation products are safe and non-toxic.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005238466990000101
    Figure BDA0005238466990000101
  • Figure BDA0005238466990000111
    Figure BDA0005238466990000111
  • Figure BDA0005238466990000121
    Figure BDA0005238466990000121
Patent Text Reader

Abstract

The present invention relates to the field of medical device materials, and in particular to a method for preparing an absorbable material for a hemostatic clip. The absorbable material for the hemostatic clip prepared by the present invention has a matrix of a magnesium alloy, which has good biocompatibility and biodegradability, and the degradation products are safe and non-toxic. An in-situ grown magnesium hydroxide coating is prepared on the surface of the magnesium alloy, and the magnesium hydroxide coating is uniform and dense, has strong bonding strength, and can resist the erosion of corrosive media in a short time. Polydopamine contains a large number of groups, among which catechol and amino groups can establish covalent and non-covalent interactions with organic-inorganic surfaces, and can improve the adhesion between the magnesium alloy matrix and modified polylactic acid. The modified polylactic acid has good biocompatibility and is ultimately metabolized into carbon dioxide and water in the body. The absorbable material for the prepared hemostatic clip has good mechanical properties, can be completely degraded and absorbed, has minimal harm to the human body, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of medical device materials, and in particular to a method for preparing an absorbable material for a hemostatic clip. Background Art

[0002] With the improvement of medical technology and the gradual change of national medical concepts, minimally invasive surgery has been accepted by more and more patients. The advantages of minimally invasive surgery are short operation time, less trauma, and quick recovery after surgery, which not only relieves the pain of patients, but also improves the overall medical efficiency. Surgical instruments with excellent hemostasis and closure capabilities are essential for every minimally invasive surgery.

[0003] Polylactic acid hemostatic clips are widely used because they are biodegradable and do not cause harm to the human body. However, the mechanical properties of polylactic acid hemostatic clips are insufficient. Therefore, in order to improve the mechanical properties of polylactic acid scaffolds, existing researchers will graft on polylactic acid or use chemical treatment methods, such as soaking the polylactic acid hemostatic clips in chemical solvents to improve the mechanical properties of polylactic acid.

[0004] Although the above method can improve the mechanical properties of the polylactic acid hemostatic clip, the surface of the polylactic acid hemostatic clip treated with chemical additives contains a certain amount of chemical substances, which will cause certain harm to the human body and also prolong the preparation time of the polylactic acid hemostatic clip. Patent technical document CN112843323A provides a polylactic acid ligation clip with added hydroxyapatite and a preparation method thereof. The polylactic acid ligation clip uses polydioxanone and polylactic acid as main components. Polydioxanone significantly reduces the processing temperature, which is beneficial to the molding and processing of polylactic acid materials. Nano-hydroxyapatite is also added, which is non-toxic and non-irritating to the human body. At the same time, it can also improve the rigidity of the polylactic acid ligation clip and overcome the brittleness of polylactic acid itself. However, the degradation rate of the prepared ligation clip is low, which is harmful to the human body.

[0005] Therefore, according to the above-mentioned related technologies, it is urgent to develop a method for preparing an absorbable material for a hemostatic clip. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a method for preparing an absorbable material for a hemostatic clip. The absorbable material for the hemostatic clip provided by the present invention has good mechanical properties, can be completely degraded and absorbed, and causes minimal harm to the human body.

[0007] Based on the above purpose, the present invention provides a method for preparing an absorbable material for a hemostatic clip.

[0008] A method for preparing an absorbable material for a hemostatic clip is as follows:

[0009] Step A1. Sodium hydroxide solution is added dropwise to make the pH value of deionized water 12-13, the polished and cleaned magnesium alloy is placed therein, heated at 125-135°C for 4-8h, ultrasonically cleaned in deionized water for 10-15min, and dried with cold air for standby use to obtain a magnesium alloy composite A;

[0010] Step A2. The pH of the dopamine solution is adjusted to 10-11 with a sodium hydroxide solution, and the magnesium alloy composite A is immersed in the dopamine solution, protected from light for 10-14 hours. After immersion, the sample is taken out, ultrasonically cleaned with deionized water for 3-5 minutes, and dried with cold air for standby use to obtain a magnesium alloy composite B;

[0011] Step A3. The modified polylactic acid is mixed with dichloromethane, stirred for 1-3 hours, the magnesium alloy composite B is immersed therein, and pulled, and the sample is taken out and dried in a drying oven at 43-48° C. for 46-50 hours to obtain an absorbable material for the hemostatic clip.

[0012] Preferably, the chemical composition of the magnesium alloy in step A1 is: Gd 5%-8%, Y 4%-6%, Zn 0.5%-1.5%, Zr 0.5%-1.5%, and the rest is Mg.

[0013] Preferably, the dosage ratio of the dopamine solution and the magnesium alloy composite A in step A2 is 200-240 mL: 15-30 g;

[0014] The dopamine solution is prepared by using dopamine hydrochloride and Tris-HCl buffer solution in a dosage ratio of 0.1-0.5 g: 100-120 mL;

[0015] The concentration of the Tris-HCl buffer solution is 10-15 mM, and the pH is 7.2-7.6.

[0016] Preferably, the mass ratio of the modified polylactic acid, dichloromethane and magnesium alloy composite B in step A3 is 8-12:200-240:15-30.

[0017] Preferably, the soaking time in step A3 is 13-15 minutes;

[0018] The pulling is performed 2-3 times in step A3, and the pulling speed is 10-15 mm / min.

[0019] Preferably, the preparation method of the modified polylactic acid is as follows:

[0020] Mix glycolide and racemic lactide, then add initiator and catalyst to mix, react for 3-5 minutes under nitrogen, then evacuate for 10-15 minutes, heat to 120-180°C, react for 12-16 hours, after the reaction, add dichloromethane, then add anhydrous methanol, precipitate for 5-8 hours, filter, and place in a vacuum drying oven to dry for 12-16 hours to obtain modified polylactic acid.

[0021] Preferably, the usage ratio of glycolide, racemic lactide, initiator, catalyst, dichloromethane and anhydrous methanol is 1-3g:4-6g:8-12mg:0.5-0.9mg:32-36mL:100-120mL.

[0022] Preferably, the initiator is any one of xylitol, arabinose, fructose and galactose.

[0023] Preferably, the catalyst is any one of stannous octoate, stannous isooctanoate, tin acetate and stannous chloride.

[0024] Beneficial effects of the present invention:

[0025] The invention provides a method for preparing an absorbable material for a hemostatic clip. The matrix of the absorbable material for the hemostatic clip prepared by the invention is a magnesium alloy, which has good biocompatibility and biodegradability, and will corrode and degrade in a physiological environment, and the degradation products are safe and non-toxic. A hydrothermal treatment modification method is adopted to prepare an in-situ grown magnesium hydroxide coating on the surface of the magnesium alloy, and the magnesium hydroxide coating is uniform and dense, has strong bonding strength, and can resist the erosion of corrosive media in a short time; polydopamine is coated on the magnesium hydroxide coating by a chemical impregnation method, and the polydopamine contains a large number of groups, among which catechol and amino groups can establish covalent and non-covalent interactions with organic-inorganic surfaces, so that the adhesion between the magnesium alloy matrix and the modified polylactic acid can be improved; the modified polylactic acid has good biocompatibility, and is finally metabolized into carbon dioxide and water in the body, and the prepared absorbable material for the hemostatic clip has good mechanical properties, can be completely degraded and absorbed, and has minimal harm to the human body. DETAILED DESCRIPTION

[0026] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0027] The sources and properties of some of the raw materials used in the present invention are as follows:

[0028] Magnesium alloy was purchased from Guizhou Anji Aviation Precision Casting Co., Ltd.; dopamine hydrochloride was purchased from Aladdin Reagent (Shanghai) Co., Ltd.; glycolide was purchased from Shanghai Yuanye Biotechnology Co., Ltd.; racemic lactide was purchased from Chongqing Yuci Pharmaceutical Technology Co., Ltd.; stannous octoate was purchased from Condis Chemical (Hubei) Co., Ltd.; stannous isooctanoate was purchased from Shanghai Myrel Biochemical Technology Co., Ltd.; tin acetate was purchased from Hubei Xinkang Pharmaceutical Chemical Co., Ltd.; and stannous chloride was purchased from Changzhou Jiaye Chemical Co., Ltd.

[0029] Embodiment 1: A method for preparing an absorbable material for a hemostatic clip, comprising the following steps:

[0030] S1. 3 g of glycolide and 6 g of racemic lactide were mixed, and then 12 mg of xylitol and 0.9 mg of stannous octoate were added and mixed, nitrogen was passed through to react for 5 min, and then vacuum was evacuated for 15 min, heated to 180 ° C, and reacted for 16 h. After the reaction, 36 mL of dichloromethane was added, and then 100 mL of anhydrous methanol was added, and precipitation was carried out for 8 h, filtered, and placed in a vacuum drying oven for 16 h to obtain modified polylactic acid;

[0031] S2. Sodium hydroxide solution was added dropwise to adjust the pH value of deionized water to 12, the polished and cleaned magnesium alloy was placed therein, heated at 125° C. for 4 h, ultrasonically cleaned in deionized water for 10-15 min, and dried with cold air for standby use to obtain a magnesium alloy composite A, wherein the chemical composition of the magnesium alloy is: Gd5%, Y4%, Zn0.5%, Zr0.5%, and the rest is Mg;

[0032] S3. Adjust the pH of 200 mL of dopamine solution to 10 with sodium hydroxide solution, soak 15 g of magnesium alloy composite A in the dopamine solution, protect from light for 10 h, take out the sample after soaking, ultrasonically clean it with deionized water for 3 min, blow dry it with cold air for standby use, and obtain magnesium alloy composite B, wherein the dopamine solution is prepared by 0.1 g of dopamine hydrochloride and 100 mL of Tris-HCl buffer solution, the concentration of Tris-HCl buffer solution is 10 mM, and the pH is 7.2;

[0033] S4. Mix 8g of modified polylactic acid with 200g of dichloromethane, stir for 1h, soak 15g of magnesium alloy composite B for 13min, pull it twice at a pulling speed of 10mm / min, take out the sample and dry it in a drying oven at 43℃ for 46h to obtain the absorbable material of the hemostatic clip.

[0034] Embodiment 2: A method for preparing an absorbable material for a hemostatic clip, comprising the following steps:

[0035] S1. 1.5 g of glycolide and 4.5 g of racemic lactide were mixed, and then 8.5 mg of arabinose and 0.6 mg of stannous isooctanoate were added and mixed, nitrogen was passed through to react for 3 min, and then vacuumed for 12 min, heated to 140 ° C, and reacted for 13 h. After the reaction, 33 mL of dichloromethane was added, and then 108 mL of anhydrous methanol was added, and precipitation was carried out for 6 h, filtered, and placed in a vacuum drying oven for 13 h to obtain modified polylactic acid;

[0036] S2. Sodium hydroxide solution was added dropwise to adjust the pH value of deionized water to 12.2, the polished and cleaned magnesium alloy was placed therein, heated at 128° C. for 4.5 h, ultrasonically cleaned in deionized water for 11 min, and dried with cold air for standby use, to obtain a magnesium alloy composite A, wherein the chemical composition of the magnesium alloy is: Gd5%, Y4%, Zn0.8%, Zr0.8%, and the rest is Mg;

[0037] S3. Adjust the pH of 210 mL of dopamine solution to 10.2 with sodium hydroxide solution, soak 18 g of magnesium alloy composite A in the dopamine solution, protect from light for 11 hours, take out the sample after soaking, ultrasonically clean it with deionized water for 3.5 minutes, blow dry it with cold air for standby use, and obtain magnesium alloy composite B, wherein the dopamine solution is prepared from 0.2 g of dopamine hydrochloride and 108 mL of Tris-HCl buffer solution, the concentration of Tris-HCl buffer solution is 11 mM, and the pH is 7.2;

[0038] S4. Mix 9g of modified polylactic acid with 210g of dichloromethane, stir for 1.5h, soak 18g of magnesium alloy composite B for 13min, pull twice at a pulling speed of 11mm / min, take out the sample and dry it in a drying oven at 43℃ for 46.5h to obtain the absorbable material of the hemostatic clip.

[0039] Embodiment 3: A method for preparing an absorbable material for a hemostatic clip, comprising the following steps:

[0040] S1. Mix 2g glycolide and 5g racemic lactide, then add 9mg fructose and 0.7mg tin acetate and mix well, react for 4min under nitrogen, then evacuate for 13min, heat to 150℃, react for 14h. After the reaction, add 34mL dichloromethane, then add 110mL anhydrous methanol, precipitate for 6.5h, filter, and dry in a vacuum oven for 14h to obtain modified polylactic acid.

[0041] S2. Sodium hydroxide solution was added dropwise to adjust the pH value of deionized water to 12.4, the polished and cleaned magnesium alloy was placed therein, heated at 130° C. for 5 h, ultrasonically cleaned in deionized water for 12 min, and dried with cold air for standby use to obtain a magnesium alloy composite A, wherein the chemical composition of the magnesium alloy is: Gd5.5%, Y4.5%, Zn1%, Zr1%, and the rest is Mg;

[0042] S3. Adjust the pH of 220 mL of dopamine solution to 10.4 with sodium hydroxide solution, soak 20 g of magnesium alloy composite A in the dopamine solution, protect from light for 12 h, take out the sample after soaking, ultrasonically clean it with deionized water for 4 min, blow dry it with cold air for standby use, and obtain magnesium alloy composite B, wherein the dopamine solution is prepared from 0.3 g of dopamine hydrochloride and 110 mL of Tris-HCl buffer solution, the concentration of Tris-HCl buffer solution is 12 mM, and the pH is 7.3;

[0043] S4. Mix 10g of modified polylactic acid with 220g of dichloromethane, stir for 1.8h, soak 20g of magnesium alloy composite B for 14min, pull twice at a pulling speed of 12mm / min, take out the sample and dry it in a drying oven at 44℃ for 47h to obtain the absorbable material of the hemostatic clip.

[0044] Embodiment 4: A method for preparing an absorbable material for a hemostatic clip, comprising the following steps:

[0045] S1. 2.5 g of glycolide and 5.5 g of racemic lactide were mixed, and then 10 mg of fructose and 0.8 mg of tin acetate were added and mixed, nitrogen was passed through to react for 4 min, and then vacuum was evacuated for 14 min, heated to 160 ° C, and reacted for 15 h. After the reaction, 35 mL of dichloromethane was added, and then 114 mL of anhydrous methanol was added, and precipitation was carried out for 7 h, filtered, and placed in a vacuum drying oven for 15 h to obtain modified polylactic acid;

[0046] S2. Sodium hydroxide solution was added dropwise to adjust the pH value of deionized water to 12.6, the polished and cleaned magnesium alloy was placed therein, heated at 132° C. for 6 h, ultrasonically cleaned in deionized water for 13 min, and dried with cold air for standby use, to obtain a magnesium alloy composite A, wherein the chemical composition of the magnesium alloy is: Gd6%, Y5%, Zn1.2%, Zr1.2%, and the rest is Mg;

[0047] S3. Adjust the pH of 230 mL of dopamine solution to 10.6 with sodium hydroxide solution, soak 25 g of magnesium alloy composite A in the dopamine solution, protect from light for 13 h, take out the sample after soaking, ultrasonically clean it with deionized water for 4.2 min, blow dry it with cold air for standby use, and obtain magnesium alloy composite B, wherein the dopamine solution is prepared from 0.4 g of dopamine hydrochloride and 114 mL of Tris-HCl buffer solution, the concentration of Tris-HCl buffer solution is 13 mM, and the pH is 7.4;

[0048] S4. Mix 11g of modified polylactic acid with 230g of dichloromethane, stir for 2h, soak 25g of magnesium alloy composite B for 14.5min, pull it 3 times at a pulling speed of 13mm / min, take out the sample and dry it in a drying oven at 45℃ for 48h to obtain the absorbable material of the hemostatic clip.

[0049] Embodiment 5: A method for preparing an absorbable material for a hemostatic clip, comprising the following steps:

[0050] S1. 2.8 g of glycolide and 5.8 g of racemic lactide were mixed, and then 11.5 mg of galactose and 0.9 mg of stannous chloride were added and mixed, and nitrogen was passed through to react for 5 min, and then vacuumed for 15 min, heated to 170 ° C, and reacted for 15.5 h. After the reaction, 35.5 mL of dichloromethane was added, and then 118 mL of anhydrous methanol was added, and precipitation was carried out for 7.5 h, filtered, and dried in a vacuum drying oven for 15.5 h to obtain modified polylactic acid;

[0051] S2. Sodium hydroxide solution was added dropwise to adjust the pH value of deionized water to 12.8, the polished and cleaned magnesium alloy was placed therein, heated at 134° C. for 7 h, ultrasonically cleaned in deionized water for 14 min, and dried with cold air for later use, to obtain a magnesium alloy composite A, wherein the chemical composition of the magnesium alloy is: Gd7%, Y5.5%, Zn1.4%, Zr1.4%, and the rest is Mg;

[0052] S3. Adjust the pH of 235 mL of dopamine solution to 10.8 with sodium hydroxide solution, soak 28 g of magnesium alloy composite A in the dopamine solution, protect from light for 13.5 h, take out the sample after soaking, ultrasonically clean it with deionized water for 4.5 min, blow dry it with cold air for standby use, and obtain magnesium alloy composite B, wherein the dopamine solution is prepared from 0.4 g of dopamine hydrochloride and 118 mL of Tris-HCl buffer solution, the concentration of Tris-HCl buffer solution is 14 mM, and the pH is 7.5;

[0053] S4. Mix 11.5g of modified polylactic acid with 235g of dichloromethane, stir for 2.5h, soak 28g of magnesium alloy composite B for 14.5min, pull it 3 times at a pulling speed of 14mm / min, take out the sample and dry it in a drying oven at 46℃ for 49h to obtain the absorbable material of the hemostatic clip.

[0054] Embodiment 6: A method for preparing an absorbable material for a hemostatic clip, comprising the following steps:

[0055] S1. Mix 3g glycolide and 6g racemic lactide, then add 12mg galactose and 0.9mg stannous chloride and mix well, react for 5min under nitrogen, then evacuate for 15min, heat to 180℃, react for 16h. After the reaction, add 36mL dichloromethane, then add 120mL anhydrous methanol, precipitate for 5-8h, filter, and dry in a vacuum oven for 16h to obtain modified polylactic acid.

[0056] S2. Sodium hydroxide solution was added dropwise to adjust the pH value of deionized water to 13, the polished and cleaned magnesium alloy was placed therein, heated at 135° C. for 8 h, ultrasonically cleaned in deionized water for 15 min, and dried with cold air for standby use to obtain a magnesium alloy composite A, wherein the chemical composition of the magnesium alloy is: Gd8%, Y6%, Zn1.5%, Zr1.5%, and the rest is Mg;

[0057] S3. Adjust the pH of 200-240 mL of dopamine solution to 11 with sodium hydroxide solution, soak 30 g of magnesium alloy composite A in the dopamine solution, protect from light for 14 h, take out the sample after soaking, ultrasonically clean it with deionized water for 5 min, blow dry it with cold air for standby use, and obtain magnesium alloy composite B, wherein the dopamine solution is prepared by 0.5 g of dopamine hydrochloride and 120 mL of Tris-HCl buffer solution, the concentration of Tris-HCl buffer solution is 15 mM, and the pH is 7.6;

[0058] S4. Mix 12g of modified polylactic acid with 240g of dichloromethane, stir for 3h, soak 30g of magnesium alloy composite B for 15min, pull it 3 times at a pulling speed of 15mm / min, take out the sample and dry it in a drying oven at 48℃ for 50h to obtain the absorbable material of the hemostatic clip.

[0059] Comparative Example 1:

[0060] Compared with Example 1, this comparative example does not add modified polylactic acid during the preparation of the absorbable material of the hemostatic clip, and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, the absorbable material of the hemostatic clip is obtained.

[0061] Comparative Example 2:

[0062] Compared with Example 1, this comparative example only replaces "modified polylactic acid" with "polylactic acid", and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, an absorbable material for the hemostatic clip is obtained.

[0063] Comparative Example 3:

[0064] Compared with Example 1, this comparative example only replaces "adding sodium hydroxide solution to make the pH value of deionized water 12" in S2 with "adding sodium hydroxide solution to make the pH value of deionized water 9", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally the absorbable material of the hemostatic clip is obtained.

[0065] Comparative Example 4:

[0066] Compared with Example 1, the step of "immersing the magnesium alloy composite A in the dopamine solution" is not performed in this comparative example, and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, the absorbable material of the hemostatic clip is obtained.

[0067] Performance Test:

[0068] Tensile properties test:

[0069] The room temperature tensile performance test of the absorbable material was carried out using a WDW-20 electronic universal testing machine, with a tensile rate of 0.5 mm / min. The absorbable materials prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were cut into samples with a length of 20 mm, a gauge length of 10 mm, and a cross-section of 2 mm×2 mm, with a tolerance range of ±0.05 mm. To ensure the accuracy of the experiment, the same composite material was subjected to three tensile tests.

[0070] Degradability test:

[0071] The absorbable material of the hemostatic clips prepared in Examples 1 to 6 and Comparative Examples 1 to 4 was made into hemostatic clips, and 60 rabbits were divided into three groups. The hemostatic clips were used to close the cystic duct and the cystic artery during open cholecystectomy, and the degradation of the hemostatic clips was observed 1 month, 2 months, 3 months, and 4 months after the operation. Five rabbits were dissected in each group at a time.

[0072] Cytotoxicity test:

[0073] Preparation of cell suspension: The cells used in this experiment are human venous endothelial cells (EC). Trypsin was added to the cultured cells, and the cells in the logarithmic growth phase were digested in the culture dish and placed in a centrifuge tube. The cells were centrifuged at 1000 rpm for 3 minutes, and the cell concentration was adjusted to prepare a cell suspension of 50,000 cells / mL;

[0074] The absorbable material of the hemostatic clips prepared in Examples 1 to 6 and Comparative Examples 1 to 4 was exposed to ultraviolet light for sterilization for 2 hours;

[0075] Extraction: 1640 was used as the cell culture medium, 10% FBS was added, and the ratio of the culture medium volume to the absorbable material surface area of ​​the hemostatic clip was 1.25 cm 2 / mL. The extract was prepared in a cell culture environment (37°C, 5% CO2, saturated humidity, sterile) for 24 hours, and the extract was filtered through a 0.22m pore size filter membrane and collected for later use. The diluent of the extract was prepared by mixing the culture medium and the extract;

[0076] Cell counting Kit-8 (CCK-8) was used for cell compatibility analysis and determination. 50,000 cells / mL were added to the wells of a 96-well plate, and after culturing for 24 hours, the cells were attached to the wall, and then the extract was changed for culturing. Subsequently, the cell activity test was performed, and the absorbance (OD value) of each well was measured at 450 by an immunomicroplate reader. Ten replicate wells were set for each group of samples, and repeated three times. Normally grown cells were used as the negative control group, and the culture medium with 10% (volume fraction) CCK-8 was added as the blank group.

[0077] 10 mL of CCK-8 reagent was added to each well. After 2 hours, the absorbance (OD value) of each well was measured at 450 nm using an immunoassay reader. The average value of 8 wells was calculated. The relative proliferation rate (RGR) of cells was calculated according to the following formula:

[0078]

[0079] RGR is the relative proliferation rate of cells, OD t is the absorbance value of the experimental group, OD nc is the absorbance value of the negative control group.

[0080] Table 1 Summary of experimental data in Examples 1 to 6 and Comparative Examples 1 to 4

[0081]

[0082]

[0083] Data Analysis:

[0084] As can be seen from Table 1, the absorbable material of the hemostatic clip prepared by the present invention has better mechanical properties, can be completely degraded in the body, and has low cytotoxicity;

[0085] This may be because the absorbable material matrix of the hemostatic clip prepared by the present invention is magnesium alloy, which has good biocompatibility and biodegradability, and will undergo corrosion degradation in a physiological environment. The degradation products are safe and non-toxic. The in-situ grown magnesium hydroxide coating is prepared on the surface of the magnesium alloy by a hydrothermal treatment modification method. The magnesium hydroxide coating is uniform and dense, has a strong bonding strength, can resist the erosion of corrosive media in a short time, and can preliminarily improve the corrosion resistance of the matrix. When only "adding sodium hydroxide solution to make the pH value of deionized water 12" in S2 is replaced by "adding sodium hydroxide solution to make the pH value of deionized water 9", it can be seen from Table 1 that the performance of the prepared material decreases. This may be because the too low solution pH value cannot generate a protective magnesium hydroxide pretreatment layer; polydopamine is coated on the magnesium hydroxide coating by a chemical impregnation method, and polydopamine Dopamine contains a large number of groups, among which catechol and amino groups can establish covalent and non-covalent interactions with organic-inorganic surfaces, so that they can strongly adhere to the surface of the substrate. Dopamine can be covalently bonded to polymers containing thiol and amino groups through Michael addition or Schiff base reaction, thereby achieving the fixation and adsorption of biological molecules and improving hemostasis. The chelation of catechol groups with metals and metal oxides helps the adhesion of polydopamine to the substrate, and it can be connected with polar polymers by forming stable hydrogen bonds. The polydopamine layer can improve the adhesion between the magnesium alloy substrate and the modified polylactic acid; the modified polylactic acid has good biocompatibility and is ultimately metabolized into carbon dioxide and water in the body. The copolymerization modification makes the interaction force between its molecular chains and the dynamic properties of the chains, which helps to disperse stress during stretching and reduce breaking points, thereby improving the overall tensile properties.

[0086] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0087] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing an absorbable material for a hemostatic clip, characterized in that: The preparation method of the absorbable material of the hemostatic clip is as follows: Step A1. Sodium hydroxide solution is added dropwise to make the pH value of deionized water 12-13, the polished and cleaned magnesium alloy is placed therein, heated at 125-135°C for 4-8h, ultrasonically cleaned in deionized water for 10-15min, and dried with cold air for standby use to obtain a magnesium alloy composite A; Step A2. The pH of the dopamine solution is adjusted to 10-11 with a sodium hydroxide solution, and the magnesium alloy composite A is immersed in the dopamine solution, protected from light for 10-14 hours. After immersion, the sample is taken out, ultrasonically cleaned with deionized water for 3-5 minutes, and dried with cold air for standby use to obtain a magnesium alloy composite B; Step A3. The modified polylactic acid is mixed with dichloromethane, stirred for 1-3 hours, the magnesium alloy composite B is immersed therein, and pulled, and the sample is taken out and dried in a drying oven at 43-48° C. for 46-50 hours to obtain an absorbable material for the hemostatic clip.

2. The method for preparing the absorbable material of the hemostatic clip according to claim 1, characterized in that: The chemical composition of the magnesium alloy in step A1 is: Gd 5%-8%, Y 4%-6%, Zn 0.5%-1.5%, Zr 0.5%-1.5%, and the rest is Mg.

3. The method for preparing the absorbable material of the hemostatic clip according to claim 1, characterized in that: The dopamine solution and the magnesium alloy composite A in step A2 are used in a ratio of 200-240 mL: 15-30 g; The dopamine solution is prepared by using dopamine hydrochloride and Tris-HCl buffer solution in a dosage ratio of 0.1-0.5 g: 100-120 mL; The concentration of the Tris-HCl buffer solution is 10-15 mM, and the pH is 7.2-7.

6.

4. The method for preparing the absorbable material of the hemostatic clip according to claim 1, characterized in that: The mass ratio of the modified polylactic acid, dichloromethane and magnesium alloy composite B in step A3 is 8-12:200-240:15-30.

5. The method for preparing the absorbable material of the hemostatic clip according to claim 1, characterized in that: The soaking time in step A3 is 13-15 minutes; The pulling is performed 2-3 times in step A3, and the pulling speed is 10-15 mm / min.

6. The method for preparing the absorbable material of the hemostatic clip according to claim 1, characterized in that: The preparation method of the modified polylactic acid is as follows: Mix glycolide and racemic lactide, then add initiator and catalyst to mix, react for 3-5 minutes under nitrogen, then evacuate for 10-15 minutes, heat to 120-180°C, react for 12-16 hours, after the reaction, add dichloromethane, then add anhydrous methanol, precipitate for 5-8 hours, filter, and place in a vacuum drying oven to dry for 12-16 hours to obtain modified polylactic acid.

7. The method for preparing the absorbable material of the hemostatic clip according to claim 6, characterized in that: The usage ratio of glycolide, racemic lactide, initiator, catalyst, dichloromethane and anhydrous methanol is 1-3g:4-6g:8-12mg:0.5-0.9mg:32-36mL:100-120mL.

8. The method for preparing the absorbable material of the hemostatic clip according to claim 6, characterized in that: The initiator is any one of xylitol, arabinose, fructose and galactose. The method for preparing the absorbable material of the hemostatic clip according to claim 6 is characterized in that: The catalyst is any one of stannous octoate, stannous isooctanoate, stannous acetate and stannous chloride.

Citation Information

Patent Citations

  • Polylactic acid ligature clip added with hydroxyapatite and preparation method of polylactic acid ligature clip

    CN112843323A